(untitled) (Fiep Bulletin - online, 2015)
Introduction: Aging produces a progressive loss of functional abilities of the body, particularly the decline of motor skills, which result in loss of independence and autonomy, greatly reducing the quality of life for seniors. Objectives: To study the correlation between handgrip strength (FPP) and performance on the Timed Up Go test (TUG) in institutionalized elderly. Methodology: A quantitative, exploratory observational study group. Sample of elderly residents in long-stay institution, where variables, gender, weight, height, BMI, and FPP TUG test were evaluated, looking for a possible correlation between the functional performance by TUG and FPP. Results: 20 participants (9 men and 11 women) were evaluated, with a mean age 69.87 ± 9.11 years. Outcomes between men and women did not differ variables analyzed, except the PPF in non-dominant hand, where women had lower values??. The main finding was the presence of a negative correlation of average statistical power between the variables in x FPP TUG test of non-dominant hand (r = -o, 690; p = 0.013) and dominant hand (r = -0.649; p = 0.005 ). Women in the study had longer institutionalization (6.3 ± 5.1 years) compared to men (4 ± 3,8anos). Conclusion: Studies related variables related to motor disorders in aging are fundamental to the advancement of scientific evidence to enable a more precise guide preventive and rehabilitative physical therapy actions. To contribute to science, are benefiting increasingly elderly population.